Non-target screening of emerging bioactive and hazardous compounds in complex matrices via multi-hyphenated techniques - Schreiner, Tamara; Justus Liebig University Giessen (My University, 2022)
Most NTS strategies for food focus on adulterations to maintain the food quality and safety. Considering thousands of unknown compounds therein, data processing is necessary to properly handle the huge amount of data. If most features of the analysed food are rationalized by processing, how can we evaluate it as safe? Therefore, new NTS strategies should prioritise bioactive compounds which is only possible by interdisciplinary hyphenation of analytical chemistry and biology. As metabolic processes can alter the bioactivity of compounds absorbed into the human body, incorporating metabolomics would provide an utmost holistic approach. The developed multi-hyphenated eight-, ten-, and twelve-dimensional workflows proved to be excellent analysis tools for the identification of new bioactive compounds from complex matrices. The more information one could gain within a comprehensive highly-streamlined workflow, the easier the elucidation of an emerging bioactive unknown is. The basic screening procedure consisted of NP-HPTLC, multi-imaging, (bio)assay, heart cut elution, online-desalting, RP-HPLC, DAD, and mass spectrometric detection (8D). Information provided by this workflow includes polarity, chromophores, UV absorption capability, native fluorescing properties, bioactivity, absorbance, and mass spectra. Extensions were introduced with the nanoGIT+active system and HRMS with fragmentation option (10D). Further dimensions were feasible through multiplexed assay formats (12D) after the diffusion susceptibility of substances in the silica gel layer was reduced with a polyisobutyl methacrylate coating. Multiplexed assays for hormonally active compounds were capable to screen for agonists, antagonists, synergists, and false-positives within a single run. Combined with the previous dimensions, comprehensive information about an unknown structure is gained, ultimately leading to structure elucidation. In conclusion, the newly developed multi-dimensional workflows are applicable both, in routine and research. They could fuel drug discovery and pharmaceutical industry, and they can serve as quality control tools to ensure food safety and prevent food fraud.
Keywords: High-performance thin-layer chromatography; High-performance liquid chromatography; Bioassay; Mass spectrometry; Multi-hyphenation; ddc:500